Increasing reaming depth enhances implant stability while minimizing bone strain - Monil Karia; Ruben Doyle; Adam Reynolds; Jonathan Jeffers; Justin Cobb (Bone & Joint Research)
Aims: Increasing the interference fit of the acetabular component can increase primary stability, but it introduces excessive periacetabular strain during impaction, which can lead to fractures. An optimal outcome following cementless acetabular component impaction is maximal primary implant stability with minimal periacetabular bone strain. The aim of this study was to investigate whether a simple modification to a surgeon’s reaming technique can achieve this desirable outcome. Methods: A custom drop rig simulated impaction strikes, seating acetabular components of either 1 mm or 2 mm interference fit into synthetic sawbones with cavities reamed to either a true hemisphere or a hemisphere with an enhanced reaming depth of 2 mm or 4 mm. Synthetic bone strain was recorded using strain gauges, and push-out tests were conducted to assess implant stability. Polar gaps were measured using optimal trackers. Results: Compared to a true hemispherical cavity, enhancing the reaming depth significantly increased the primary stability of the implant (p < 0.001) while reducing both the periacetabular strain and strain deterioration for both 1 mm and 2 mm interference fit components. A 4 mm reaming depth enhanced the primary stability of 1 mm press-fit components to a level almost equivalent to a 2 mm press-fit, albeit reducing strain to the bone. Enhancing reaming depth did not significantly affect polar gap. Conclusion: Enhancing cavity reaming depth is a simple technique to increase the implant primary stability of press-fit uncemented acetabular components, while avoiding any excess in periacetabular strain and the associated fracture risk. Cite this article: Bone Joint Res 2025;14(6):551–559.